EDUCAÇÃO AMBIENTAL: ALUNOS DA EJA PRATICAM A POLÍTICA DOS 3R’S NA EEEFM BARTOUVINO COSTA EM LINHARES-ES (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
The cultural industry has influenced humans to exaggerate consumerism, as a consequence, there is an increase in Garbage, the pivot of the great environmental problems that the Earth faces daily. Therefore, this project was carried out with the Education of Youth and Adults - EJA, with a view to discussing how to give a better destination to garbage, minimizing environmental impacts in the school environment. Based on this proposal, the project “Environmental education: EJA students practice the '3Rs' policy at EEEFM 'Bartouvino Costa' in Linhares-ES was developed. With the objective of sensitizing students about the environmental problems caused by garbage, adopting initiatives that minimize such problems and that seek to transform garbage into useful everyday objects. The methodology of dialogued expository classes was adopted to expose the problem, study actions to be developed and understand the main biological concepts about this theme. Recycling workshops were developed with the students, so that, on the day the project was completed, the objects produced and the benefits of this practice could be exposed to the school community, encouraging the permanent adoption of this attitude. Students were evaluated quantitatively and qualitatively, which resulted in learning essential biological concepts for academic training and the correct ways to treat waste.
Keywords: Environmental Education; 3R's; Garbage